OPTIMIZING THE APPLICATION OF OCCUPATIONAL SAFETY AND HEALTH (K3) CULTURE IN THE LEARNING PROCESS OF MECHANICAL ENGINEERING PRACTICE - Khakam Ma'ruf; Rizal Justian Setiawan; Darmono Darmono; Nur Evirda Khosyiati; Nur Azizah (Program Studi PGSD Universitas Flores, 2024)
The implementation of OSH in the workplace is a necessity for companies or institutions that brings great benefits to all workers and is not felt as a burdensome burden but rather awareness of workers from the risk of materials. Indonesia still has a low level of work safety when compared to developed countries, this makes the risk and level of work accidents in Indonesia still high. This study aims to find solutions to the problems that hinder the application of OHS in mechanical engineering practice. This study uses a qualitative approach to describe the application of occupational safety and health in the mechanical engineering workshop, descriptive methods used in this study, in the form of interviews, observations, and documentation to collect the necessary data. SMK Negeri 2 Pengasih has included K3 planning as a guideline for implementing practical learning in the workshop. Teacher supervision and guidance in its application is quite good regarding the work to be done. However, OHS evaluation has not been fully conducted in practical learning at school. This is related to policy and improvement of evaluation development as a basis for implementing further learning. From the evaluation, shortcomings can be identified so that better planning can be made for workshop practice for students of SMK N 2 Pengasih.